National Reports on the Transfer of Movables in Europe : Volume 4: France, Belgium, Bulgaria, Poland, Portugal. - Faber, Wolfgang (Sellier. european law Publishers, 2010)
HauptbeschreibungThis excellent series presents comparative study, analysis and evaluation of 28 European legal systems in the field of transfer of movables. Major topics are - the notion of ownership, - the derivative acquisition of ownership (e.g. by a sales contract), - the good faith acquisition of ownership and other property rights, - the multiple sale of the same movable, - the protection of possession, positive (acquisitive) prescription, and- processing and consolidation. The work is based on comprehensive country reports (which are to be published) on the relevant legal rules in.